Granulometria e processamento de dietas para leitões dos 23 aos 71 dias de idade - Clarice Speridião Silva Neta (2015)
An experiment was conducted with the objective to evaluate the effect of diets with different particle sizes and processing on the performance of piglets weaned at 23 days old and its economic viability. We used 120 piglets from commercial lineages with initial weight 6.65 ± 0.20 kg of 23 to 71 days old. The animals were distributed in a completely randomized design with six treatments and five replications and four animals per experimental unit, two castrated males and two females. The periods were evaluated: 23 to 37 days, 23 to 51 days and total period. The treatments consisted of two ground rations in 1.2 mm sieve (FF) and 2.5 mm (FG) and three feed processed in the form micropelltets (MP), thick pelletized (PG) and pelletized subsequently crushed (PT). There were no significant differences (P>0.05) between treatments for variables, weight to 23, 37 and 71 days, but there were differences (P<0.05) to weight to 51 days, being that diets MP, PG and PT contributed to heavier piglets. There was no effect (P>0.05) on daily weight gain (GPD) and average daily consumption (CMD) of 23 to 37 days. However, there was difference (P<0.05) for the feed conversion (CA), being better for the treatments MP, PG and PT. Of the 23 to 51 days, there was no difference (P>0.05) for the CMD, but for the GPD and the CA was difference (P<0.05) to diets MP, PG and PT regarding diets FF and FG. Of the 23 to 71 days no difference (P>0.05) was found for any of the variables studied. Therefore, it is concluded that diets MP, PG and PT showed best results of CA during 23 to 37 and 23 to 51 days compared to FF and FG. In this last period, the weight and the GPD also were better for diets MP, PG and PT, demonstrating the efficiency of processing. Among the processed treatments, no significant differences (P>0.05) for any of the variables. Therefore, it is concluded that processed diets contributed to better results of performance up to 51 days old, this effect being lost in the total period, independent of particle size. The processing, allowed reduction in cost/Kg of animal produced only in the first phase (23 to 37 days of age).